Near-identical star formation rate densities from Hα and FUVat redshift zero. Issue 1 (12th June 2018) - Audcent-Ross, Fiona M; Meurer, Gerhardt R; Wong, O I; Zheng, Z; Hanish, D; Zwaan, M A; Bland-Hawthorn, J; Elagali, A; Meyer, M; Putman, M E; Ryan-Weber, E V; Sweet, S M; et al.
ABSTRACT: For the first time both H α and far-ultraviolet (FUV) observations from an H i -selected sample are used to determine the dust-corrected star formation rate density (SFRD: ρ ) in the local Universe. Applying the two star formation rate indicators on 294 local galaxies, we determine log(ρ _ Hα ) = -1.68^+0.13_-0.05 [M⊙ yr −1 Mpc −3 ] and log(ρ _ FUV ) = -1.71^+0.12_-0.13 [M⊙ yr −1 Mpc −3 ]. These values are derived from scaling H α and FUV observations to the H i mass function. Galaxies were selected to uniformly sample the full H i mass (M_H I ) range of the H i Parkes All-Sky Survey (M_H I 10^7 to ∼10 10.7 M⊙ ). The approach leads to relatively larger sampling of dwarf galaxies compared to optically selected surveys. The low H i mass, low luminosity, and low surface brightness galaxy populations have, on average, lower H α /FUV flux ratios than the remaining galaxy populations, consistent with the earlier results of Meurer. The near-identical H α - and FUV-derived SFRD values arise with the low H α /FUV flux ratios of some galaxies being offset by enhanced H α from the brightest and high mass galaxy populations. Our findings confirm the necessity to fully sample the H i mass range for a complete census of local star formation to include lower stellar mass galaxies which dominate the local Universe.